The Resistance of states system against nonstate violence: International cooperation to preserve state monopoly of force - Kaya, Erdem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
With the combined impact of the phenomena of state failure and globalization in the post-Cold War period, violent nonstate actors (warlords, militias, terrorist organizations, insurgents, pirates, transnational criminal organizations) in general became transnational players. As the violent nonstate actors threatened the security of more states other than the targeted one(s), governments tended to work together to fight against them. Governments cooperated through diverse methods to re-establish and to preserve state monopoly on the use of violence against the challenge of these actors. Particularly since the late 1990s, states have been forming an international security regime against nonstate violence through mainly multilateral conventions and UN Security Council resolutions. Within the framework of this anti-nonstate violence security regime, cooperation among states is performed via the United Nations and other international, regional and sub-regional intergovernmental organizations. This study contends that the security regime-facilitated international cooperation works to preserve state monopoly of force, which is the main building-block of the existing states system. Therefore, states system has been developing a resistance against nonstate actors’ resurgence to posses the means of large-scale violence.
Keywords: Terrorism.; Terrorism -- Prevention -- Government policy.; Terrorism -- Prevention -- International cooperation.